Comparative analysis of the feline immunoglobulin repertoire. (March 2017) - Steiniger, Sebastian C.J.; Glanville, Jacob; Harris, Douglas W.; Wilson, Thomas L.; Ippolito, Gregory C.; Dunham, Steven A.
Abstract: Next-Generation Sequencing combined with bioinformatics is a powerful tool for analyzing the large number of DNA sequences present in the expressed antibody repertoire and these data sets can be used to advance a number of research areas including antibody discovery and engineering. The accurate measurement of the immune repertoire sequence composition, diversity and abundance is important for understanding the repertoire response in infections, vaccinations and cancer immunology and could also be useful for elucidating novel molecular targets. In this study 4 individual domestic cats ( Felis catus ) were subjected to antibody repertoire sequencing with total number of sequences generated 1079863 for VH for IgG, 1050824 VH for IgM, 569518 for VK and 450195 for VL. Our analysis suggests that a similar VDJ expression patterns exists across all cats. Similar to the canine repertoire, the feline repertoire is dominated by a single subgroup, namely VH3. The antibody paratope of felines showed similar amino acid variation when compared to human, mouse and canine counterparts. All animals show a similarly skewed VH CDR-H3 profile and, when compared to canine, human and mouse, distinct differences are observed. Our study represents the first attempt to characterize sequence diversity in the expressed feline antibody repertoire and this demonstrates the utility of using NGS to elucidate entire antibody repertoires from individual animals. These data provide significant insight into understanding the feline immune system function.